EFEKTIFITAS PENGELUARAN PEMERINTAH (GOVERMENT EXPENDICTURE) TERHADAP PENYERAPAN TENAGA KERJA DI KABUPATEN JEMBER - Laksono, Richat Tri (BISMA: Jurnal Bisnis dan Manajemen, 2016)
Abstract: This paper aims to find out the goverment expendicture against the absorption of labor in Jember Regency. The methodology used is based secondary data from various official sources whereas the sample used was for the period 2004-2013. Data analysis tools applied in this study is a method of \the trend analysis and bivariate Correlation. The results of the analysis of the obtained answers that the absorption of labor in Jember Regency will increase while the correlation between Jember Regency Government spending with the absorption of labor in Jember Regency is very strong and direct. Keywords: Labour, The Allocation Of Budget Revenues And Shopping Regency (APBD), Jember